Spontaneous pregnancy after tracking ovulation during menstruation: A case report of a woman with premature ovarian insufficiency and repeated failure of in vitro fertilization - He, Ye; Wang, Wanlu; Wu, Chunmei; Li, Wenwen; Liu, Hongjiang; Wei, Zhaolian (Frontiers in Medicine, 2022)
The diagnosis of premature ovarian insufficiency (POI) is devastating in women of reproductive age because of the small chance of spontaneous pregnancy. Here, we report a very rare case with POI and repeated failure of in vitro fertilization (IVF) where the final result was natural fertilization following guidance to have sexual intercourse during menstruation as ovulation was monitored. Estradiol valerate was used to increase the thickness of the endometrium and stop the menstrual bleeding. There was a serum level of 208.44 IU/L of human chorionic gonadotropin (HCG) 14 days after the ovulation. Later, a series of transvaginal ultrasounds also indicated a normal-appearing intra-uterine pregnancy. A healthy baby girl was delivered at term by means of cesarean section. Our report suggested that although the chance of spontaneous pregnancy is relatively low in patients with POI with repeated IVF failures, as long as ovulation does occur, even if it happens during menstruation, natural pregnancy is still worth trying with a series of proper and personalized treatments.